Forged in America: how Irish-Jewish encounters shaped a nation - Diner, Hasia R.; Nyhan Grey, Miriam (The Goldstein-Goren series in American Jewish history, 2023)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Foreword: A Good Place to Meet -- Introduction: Forged in America -- 1. A Singular Encounter: Irish and Jews in Their American Home -- 2. The Right to Choose: The Public Health and Birth Control Movements of Lillian Wald and Margaret Sanger -- 3. "Tammany's Chosen People": How the Irish Courted the Jewish Vote in Progressive-Era New York -- 4. Jews, Paul O'Dwyer, and a New York Life -- 5. Defending Literary Genius: James Joyce's Ulysses on Trial -- 6. Laughter and Love between the Irish and the Jews -- 7. Irish-Jewish Couples in American Film and Television -- 8. Playing the Nation: Constructing Cultural Revivals in the Irish and the Jewish Diaspora -- 9. The Irish, the Jews, and Wilson's "Self-Determination" -- 10. A Tradition of Acceptance: Jews and Their Basketball Players at an Irish Catholic College -- Acknowledgments -- Notes -- About the Editors -- About the Contributors -- Index.